Schwann Cell Glycogen Selectively Supports Myelinated Axon Function - Brown, Angus M (2012)
OBJECTIVES: Interruption of energy supply to peripheral axons is a cause of axon loss. We determined if glycogen was present in mammalian peripheral nerve, and if it supported axon conduction during aglycemia. METHODS: We used biochemical assay and electron microscopy to determine the presence of glycogen, and electrophysiology to monitor axon function. RESULTS: Glycogen was present in sciatic nerve, its concentration varying directly with ambient [glucose]. Electron microscopy detected glycogen granules primarily in myelinating Schwann cell cytoplasm and these diminished after exposure to aglycemia. During aglycemia, conduction failure in large myelinated axons (A fibers) mirrored the time-course of glycogen loss. Latency to CAP failure was directly related to nerve glycogen content at aglycemia onset. Glycogen did not benefit the function of slow-conducting, small diameter unmyelinated axons (C fibers) during aglycemia. Blocking glycogen breakdown pharmacologically accelerated CAP failure during aglycemia in A fibers, but not in C fibers. Lactate was as effective as glucose in supporting sciatic nerve function, and was continuously released into the extracellular space in the presence of glucose and fell rapidly during aglycemia. INTERPRETATION: Our findings indicated that glycogen is present in peripheral nerve, primarily in myelinating Schwann cells, and exclusively supports large diameter, myelinated axon conduction during aglycemia. Available evidence suggests that peripheral nerve glycogen breaks down during aglycemia and is passed, probably as lactate, to myelinated axons to support function. Unmyelinated axons are not protected by glycogen and are more vulnerable to dysfunction during periods of hypoglycemia.